Resistant Starch but Not Enzymatically Modified Waxy Maize Delays Development of Diabetes in Zucker Diabetic Fatty Rats. Issue 5 (15th March 2017) - Hedemann, Mette Skou; Hermansen, Kjeld; Pedersen, Sven; Bach Knudsen, Knud Erik
Abstract: Background: The incidence of type 2 diabetes (T2D) is increasing worldwide, and nutritional management of circulating glucose may be a strategic tool in the prevention of T2D. Objective: We studied whether enzymatically modified waxy maize with an increased degree of branching delayed the onset of diabetes in male Zucker diabetic fatty (ZDF) rats. Methods: Forty-eight male ZDF rats, aged 5 wk, were divided into 4 groups and fed experimental diets for 9 wk that contained 52.95% starch: gelatinized corn starch (S), glucidex (GLU), resistant starch (RS), or enzymatically modified starch (EMS). Blood glucose after feed deprivation was assessed every second week; blood samples taken at run-in and at the end of the experiment were analyzed for glycated hemoglobin (HbA1c) and plasma glucose, insulin, and lipids. During weeks 2 and 8, urine was collected for metabolomic analysis. Results: Based on blood glucose concentrations in feed-deprived rats, none of the groups developed diabetes. However, in week 9, plasma glucose after feed deprivation was significantly lower in rats fed the S and RS diets (13.5 mmol/L) than in rats fed the GLU and EMS diets (17.0–18.9 mmol/L), and rats fed RS had lower HbA1c (4.9%) than rats fed the S, GLU, and EMS (5.6–6.1%) diets. The homeostasis model assessment of insulin resistance was significantly lower in rats fed RS than in rats fed the other diets (185 compared with 311–360), indicating that rats fed the S, GLU, and EMS diets were diabetic, and a 100% higher urine excretion during week 8 in rats fed the GLU and EMS diets than that of rats fed S and RS showed that they were diabetic. Urinary nontargeted metabolomics revealed that the diabetic state of rats fed S, GLU, and EMS diets influenced microbial metabolism, as well as amino acid, lipid, and vitamin metabolism. Conclusions: EMS did not delay the onset of diabetes in ZDF rats, whereas rats fed RS showed no signs of diabetes.